The Effect of Local Community Empowerment on Digital Transformation in Cultural and Tourism Preservation - Astuti, Devita; Kisworo, Bagus; Olayinka Shogbesan, Yusuf; Herwina, Wiwin (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Digital transformation today is used in everyday life, from communicating, shopping, promoting a product or activity, and transportation. This study aimed to understand the effect of local community empowerment on digital transformation in preserving culture and tourism in Lempongsari Village. This research uses SPSSv.23 to analyze the simple linear regression test and to display percentages based on the Likert Scale (1-5). The simple linear regression test aims to determine whether local community empowerment affects digital transformation. The research method used is quantitative with an ex post facto research design. The results of this study indicate that local community empowerment influences the digital transformation of preserving culture and tourism in Lempongsari Village. These results were obtained after going through several simple linear regression tests: normality, linearity, and heteroscedasticity. In addition, this study also uses the Likert scale test, and the results show that in the community empowerment variable, the highest score is in the high category with a total of 92.6%, and the rest is in the very high category with a total of 7.4%. Meanwhile, in the digital transformation variable, the highest score is the high category, with a total of 97%, and the rest is the medium category, with a total of 7%. This research can be a reference for the village government and the central government to pay more attention to the community regarding the importance of digital technology in everyday life through empowerment.